The types of ethical climate as related to missed nursing care in cancer care units - Vryonides, Stavros; Merkouris, Anastasios; Charalambous, Andreas; Eleftheriou, Christos; Andreou, Panayiota; Papastavrou, Evridiki (My University, 2017)
Ethical Climate is actually a dimension ofthe whole working environment and the theory suggests that the types of Ethical Climate that exist in an organization reflects the collective ethical behaviorofthe employees in this organization(Victor& Cullen, 1987).
Keywords: Quality care; Working environment; Health care